OP76 The relationship between life course socio-economic position and quality of life among Europeans in early old age: the role of the welfare regime and current financial distress. (2nd September 2014) - Niedzwiedz, CL; Pell, JP; Mitchell, R
Abstract : Background: Life course socio-economic position is associated with a number of adverse health outcomes in older people. However, whether an increased number of socio-economically advantaged positions throughout the life course is associated with higher subjective quality of life has not been established. Societies that have differing welfare state arrangements may also vary in their ability to modify the relationship between socio-economic conditions over the life course and quality of life. This study addressed three key questions: (1) Is increased socio-economic advantage over the life course associated with higher quality of life in early old age? (2) Does the welfare regime moderate this association? (3) Can the relationship be explained by current financial distress? Methods: Data were derived from individuals (n=14, 789) aged 50 to 75 years resident in 13 European countries (representing four welfare regimes) participating in wave 2 of the Survey of Health, Ageing, and Retirement in Europe (SHARE) and SHARELIFE (the retrospective wave). Quality of life was measured by CASP-12 (control, autonomy, self-realisation and pleasure) and life satisfaction (as a sensitivity analysis). A composite life course socio-economic advantage score was generated from four childhood and four adulthood socio-economic variables. Individuals were given a score ranging from 0 to 8 based on the sum of their relative rank in the cumulative population distribution for each socio-economic variable, taking into account the differing socio-economic distributions by country, gender and cohort. Age-adjusted multilevel linear regression models stratified by gender were calculated, including interaction terms between the life course advantage scores and the welfare regime. Models stratified by welfare regime were also calculated, which adjusted for financial distress. Results: A greater number of socio-economically advantaged positions over the life course was associated with higher quality of life in early old age. Among men, a one-unit increase in the life course socio-economic advantage scale was associated with 0.74 (95% CI: 0.64 to 0.84) higher CASP-12 scores and the equivalent result among women was 0.87 (95% CI: 0.78 to 0.97). The association between the life course socio-economic advantage score and quality of life was weaker in the Scandinavian regime and stronger in Southern and post-communist regimes. Including financial distress greatly attenuated the association in all welfare regimes. Conclusion: Higher quality of life during early old age was related to greater socio-economic advantage throughout the life course. Interventions that buffer financial distress in early old age may be beneficial for improving quality of life and producing a more equitable distribution.